Keputusan Investasi Gen Z Dengan Literasi Keuangan Sebagai Variabel Moderasi - Budiman, Johny; Jofia, Nurul; Salim, Silvia; Sitorus, Winda Fionita (Universitas Multi Data Palembang, 2024)
Internet use is also increasingly widespread in various fields, including finance which is increasingly common. Financial literacy is very important for everyone, especially people who carry out investment activities because apart from increasing knowledge about finances or investments, it can also protect us from fraud. The aim of this research is to find out what factors influence generation Z's investment decisions and the importance of financial literacy in doing business. The method used is a quantitative method by distributing questionnaires online to respondents. The data analysis methods used are empirical, descriptive statistical methods, correlation analysis, simple regression, and multiple regression tests. Generation Z as investors have different investment characteristics and behavior. Herding bias, disposition effect, overconfidence, and financial literacy play an important role in shaping investors' investment decisions.